Kur’an’da ve Kitab-ı Mukaddes’te mesih - Demir, Rıdvan (My University, 2003)
Tezimiz bir giriş üç ana bölüm ve bir sonuçtan oluşmaktadır. Giriş bölümünde dinlerde kurtarıcı müjde ve beklentisini inceledik, bu inancın tarihin, ilk olarak nasıl ortaya çıktığını ve bir dinden diğerine nasıl geçtiğini araştırdık. Birinci Bölümü Eski Ahid'de mesih inancına ayırdık. Mesih kelimesinin etimolojik yapını ve anlamalarını verdikten sonra, Eski Ahid'de mesih kelimesinin nasıl kullanıldığına ve inancı ifade etmek için kullanılan yakın kelimelere yer verdik. Mesih beklentisinin kaynağını ve özelliklerini tespit ettik. Neviim (peygamber kitaplarında) kral kelimesinin kullanımına ve Mesih ile Tanrı Yahve'nin ilişkisine değindik. Mesih müjdesinin Eski Ahid'in Tevrat, Neviim ve Ketuvim (kitaplar) bölümlerindeki kullanımlarını tespite çalıştık. Mesih'in özelliklerini ve onun döneminde neler olacağına ilişkin bilgiler sunduk. İkinci Bölümde Yeni Ahid'de mesih inancını ele aldık. İncillere ve Yeni Ahid mektuplarına göre İsa'nın mesih oluşunu inceledik. Ardından İsa Mesih'in; mesih, Tarırı'nın oğlu, insanoğlu, kurtarıcı, rab, Davud soyundan bir kral oluşu gibi özelliklerini ortaya koyduk. Bu bölümde son olarak İsa Mesih'in tüm evreni ve insanları yargılamak için yeryüzüne ikinci dönüşüne ilişkin Yeni Ahid'den referanslar verdik. Üçüncü Bölümde Kur'ân'da mesih kelimesinin kullanımına ve mesih inancının bulunup bulunmadığına yer verdik. Daha önceki dinlerde konu edinilen beklenen kurtarıcının İslam peygamberi Hz. Muhammed olduğu sonucuna vardık. Son peygamber olan Hz. Muhammed de peygamberlik görevini tamamlayarak bu dünyadan ayrılmıştır. Dolayısıyla bundan böyle herhangi bir peygamberin (veya mesihin) kurtarıcı olarak geri gelmesi söz konusu değildir. Sonuç bölümünde ise Kitab-ı Mukaddes ve Kur'ân-ı Kerim'in yaklaşımlarını özetledikten sonra, ulaştığımız kişisel kanaatleri ortaya koymaya çalıştık.

This thesis consists of an introduction, three main bodies and a conclusion. In the introduction, we examined the goodnews of the saviour and his expectations, the history of this belief and how it came about at fırst sight and how it transferred to the other religions. In the first part, we gave place to the Messiah Belief in the Old Testament. After giving the meaning and the etymological structure of the word Messiah, we focused on how to use this word and other words related to it. We identifıed the source and the properties of these expectations. Through the Neviim (prophet books), we touched on the subjects such as the usage of the word the king and the relationship between messiah and Yahve Adonay. Moreover we tried to establish the usage of messiah goodnews in the section of the New Testament such as Torah, Neviim and Ketuvim (books). We presented the features of messiah, and concerning what is going to happen in his period. In the second part, we looked at the belief of messiah in the New Testament we examined Jesus's becoming a messiah according to the Gospells and the letters of the New Testament. Following we put forward Jesus Christ's different features; messiah, the son of God, a humanbeing, saviour, God, king, the descendant from the family of David. In this part, as a conclusion we gave some references concerning Jesus Christ's returning to the world for the second time in order to judge all the human beings and the whole universe. In the third part we gave part to the usage of the word messiah and whether there is a belief of messiah or not in the Quran. We came up with the conclusion that the prophet of Islam Muhammed is the one who is talked about in the previous religions as the expected saviour. The last prophet Muhammed left the world after he had completed his prophethood duty. Consequenty, it is impossible to speak about the returning of any prophet (or messiah) as a saviour from here on in. In the conclusion part, after summerizing the approaches of the Bible and the Quran, we tried to put forward the personal convictions we reached
Keywords: Din; İslam; İslam Dini